Effect Of Twist Drill Geometry And Drilling Parameters On Thrust Force In Single-Shot Drilling Of Stack-Up Material - Chim, Yi Shen (Universiti Sains Malaysia, 2017)
Stacked up drilling is being practiced widely in the aerospace industry, but the compatibility of the drill to compensate the widely differing properties of composite and metal is still a major challenge to the industry. In this study, the effect of the twist drill geometry and drilling parameters are being investigated based on the generation of thrust force signature during drilling of CFRP/Al. Based on ANOVA, it is found that the thrust force for both Aluminum and CFRP are highly dependent on feed rate. Through the analysis of thrust force, supported by hole diameter, surface roughness and chip formation, it is concluded that the optimum tool parameters selection includes helix angle of 30°, primary clearance of 6°, point angle of 130°, chisel edge angle of 30°, speed of 2600 rpm and feed rate of 0.05 mm/rev. At the same time, the optimum parameters obtained in this study is verified of its capability to produce higher hole quality and efficiency compare to customer requirement, which set the parameters as 2600 rpm for speed and 0.1 mm/rev for feed rate.